The transport coefficients for slow collective motion - F. A. Ivanyuk (Ядерна фізика та енергетика)
We study the collective motion of iso-scalar type at finite excitations and concentrate on slow motion, due to the presence of a strong friction force. In the present talk the extension of approach to the case of low excitation energies, where shell effects and pairing correlation are important, is reviewed. The case of rotating nuclei is also included. As an application of the theory, the numerical results are presented for the transport coefficients for few composite systems formed in the so called warm fusion reactions used for the synthesis of the super heavy systems.